KPU treating agent for processing scratch-resistant and anti-collision gloves and preparation method of KPU treating agent

By preparing specific components and combining KPU treatment agents, the problem of insufficient performance of traditional KPU treatment agents in scratch-resistant and collision-resistant glove processing is solved, achieving better scratch-resistant and collision-resistant performance, as well as higher production efficiency.

CN120041074APending Publication Date: 2025-05-27江苏昌邦安防科技股份有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510301722.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-14
Publication Date
2025-05-27

AI Technical Summary

Technical Problem

In the processing of traditional KPU treatment agents, there are problems such as limited scratch resistance, unsatisfactory anti-collision effect, and slow curing, resulting in low production efficiency.

Method used

By preparing end-hydroxyl polyurethane prepolymer, end-amino polyurea prepolymer, surface-treated ceramic particles and starch composite carbon nanotubes, and mixing at suitable temperatures and conditions, component A is combined with component B containing diisocyanate and catalyst to form a KPU treatment agent, applied to the surface of the glove and cured.

Benefits of technology

It improves the adhesion between the KPU treatment agent and the glove, enhances the scratch resistance and collision resistance of the gloves, and improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120041074A_ABST
    Figure CN120041074A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of KPU treating agents, in particular to a KPU treating agent for processing scratch-resistant and anti-collision gloves and a preparation method of the KPU treating agent. The prepared KPU treating agent is used for treating gloves, and the problems that the gloves are poor in scratch resistance and anti-collision performance are solved. The preparation method comprises the following steps: preparing a hydroxyl-terminated polyurethane prepolymer, an amino-terminated polyurea prepolymer, surface-treated ceramic particles and a starch composite carbon nanotube, mixing the components at proper temperature and under proper conditions to obtain a component A, mixing the component A with a component B containing diisocyanate and a catalyst, and carrying out extrusion molding to obtain the polyurethane composite material. The glove treated by the KPU treating agent is obtained by brushing each part of the glove with the KPU treating agent, and the glove has good scratch resistance and anti-collision effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of KPU treating agents, in particular to a KPU treating agent for processing scratch-resistant and collision-resistant gloves and a preparation method thereof. Background Art

[0002] KPU treatment agent, as a chemical agent used to improve the surface properties of materials, has received widespread attention in recent years. KPU treatment agent improves the smoothness, glossiness, adhesion and mechanical properties of materials by forming a coating on the surface of the material, and is used in many fields such as automotive paint, plastic products, leather and gloves.

[0003] In the glove processing industry, especially for the production of scratch-resistant and anti-collision gloves, the traditional KPU treatment agent has many shortcomings when used for the processing of scratch-resistant and anti-collision gloves. On the one hand, the scratch resistance of the treated gloves is limited. In actual use, after a short period of friction contact, scratches are easily formed on the surface of the gloves, affecting the protective performance and aesthetics of the gloves; on the other hand, its anti-collision effect is not ideal, and it cannot effectively absorb and disperse the impact force, and the protective effect on the hands is weak; in addition, in terms of the wearing performance of the gloves, if the KPU treatment agent cures slowly, the glove molding time is long during the production process, which may lead to low production efficiency and fail to meet the large market demand. Moreover, incomplete curing may cause the treatment agent coating to be not firmly bonded to the glove base material. During daily wearing, the gloves are frequently bent and rubbed, and the coating is easy to fall off, which not only affects the appearance of the gloves, but also reduces the protective performance of the gloves. The gloves treated with the existing KPU treatment agent have the problems of poor scratch resistance and poor anti-collision performance.

[0004] Therefore, a KPU treating agent for processing scratch-resistant and collision-resistant gloves and a preparation method thereof are proposed. Summary of the invention

[0005] The purpose of the present invention is to provide a KPU treatment agent for processing scratch-resistant and anti-collision gloves and a preparation method thereof, wherein hydroxyl-terminated polyurethane prepolymer, amino-terminated polyurea prepolymer, surface-treated ceramic particles and starch composite carbon nanotubes are prepared, and the above components are mixed under suitable temperature and conditions to obtain component A, and component A is mixed with component B containing diisocyanate and catalyst, and then brushed on various parts of the gloves to obtain gloves treated with the KPU treatment agent. By optimizing the preparation method of hydroxyl-terminated polyurethane prepolymer, amino-terminated polyurea prepolymer, surface-treated ceramic particles and starch composite carbon nanotubes, and adjusting the mixing process conditions, the KPU treatment agent and the gloves have strong adhesion; at the same time, the gloves treated with the KPU treatment agent have good scratch resistance and anti-collision effect.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a KPU treating agent for processing scratch-resistant and collision-resistant gloves. The preparation method is as follows:

[0008] Add 8.0-12.0 parts of surface-treated ceramic particles to 48-55 parts of hydroxyl-terminated polyurethane prepolymer and dimethyl carbonate, increase the rotation speed to 400 rpm, lower the temperature to 40-50° C. after stirring, add 8.5-14 parts of starch composite carbon nanotubes, keep the rotation speed at 250-330 rpm, continue stirring, add 4-8 parts of amino silicone oil, stir at 50° C. and 250 rpm for 30 minutes, finally add 55-62 parts of amino-terminated polyurea prepolymer, stir and mix to obtain component A;

[0009] 17.8-21.1 parts of diisocyanate solution and 0.3-0.6 parts of catalyst are mixed to obtain component B; component A and component B are mixed evenly at a speed of 350-450 rpm to obtain a KPU treatment agent precursor; the KPU treatment agent precursor is diluted to a viscosity of 1500-2500 mPa·s to obtain a KPU treatment agent for processing scratch-resistant and anti-collision gloves;

[0010] The amino-terminated polyurea prepolymer is obtained by the reaction of itaconic anhydride, fluorinated alcohol and fluorinated diamine; the hydroxyl-terminated polyurethane prepolymer is obtained by the reaction of polypropylene glycol, 1,4-cyclohexanediol, hexamethylene diisocyanate and polyethylene glycol; and the starch composite carbon nanotubes are obtained by the reaction of starch, γ-chloropropyltrimethoxysilane, polyepichlorohydrin-dimethylamine and carboxyl carbon nanotubes.

[0011] Preferably, the preparation method of surface-treated ceramic particles is as follows: ceramic particles with average particle sizes of 10 μm, 50 μm and 100 μm are mixed in a mass ratio of 5-14:4-10:1 to obtain mixed ceramic particles; the mixed ceramic particles are acid-etched using a 5% hydrofluoric acid aqueous solution, reacted for 15-25 minutes, filtered, washed with water, and dried to obtain acid-etched ceramic particles; 30 parts of the acid-etched ceramic particles are added to 40-60 parts of hydroxyethyl acrylate, and 0.2-0.5 parts of benzoyl peroxide are added, mixed evenly, and reacted at 60-80°C for 2-4 hours; after cooling to room temperature, washed with water and dried to obtain surface-treated ceramic particles.

[0012] Preferably, the α-Al in the ceramic particles 2 O 3 The crystalline phase accounts for 71.2%, TiO 2 The rutile phase accounts for 26.8%.

[0013] Preferably, the preparation method of the terminal hydroxyl polyurethane prepolymer is as follows: polypropylene glycol and 1,4-cyclohexanediol are mixed with hexamethylene diisocyanate and reacted, polyethylene glycol is added after the reaction is completed, and the reaction is continued for 3 hours to obtain the terminal hydroxyl polyurethane prepolymer; the mixing molar ratio of polypropylene glycol, 1,4-cyclohexanediol, hexamethylene diisocyanate and polyethylene glycol is 5-7:3-5:11-12:1-3.

[0014] Preferably, the preparation method of the amino-terminated polyurea prepolymer is as follows: itaconic anhydride and a fluorine-containing alcohol are added to a three-necked flask in a molar ratio of 1:2-2.3, and after stirring evenly, aminosulfonic acid and toluene are added. The water generated during the reaction is removed through a water separator, and after the reaction is completed, toluene is removed to obtain a fluorine-containing itaconate; the fluorine-containing itaconate is added dropwise to the melted fluorine-containing diamine; the molar ratio of the fluorine-containing diamine to the fluorine-containing itaconate is 1:2-2.2, the temperature is raised to 60°C, and the reaction is carried out for 5 hours to obtain an amino-terminated polyurea prepolymer; the fluorine-containing alcohol is 1H,1H,8H,8H-octafluoro-3,6-dioxa-1,8-octanediol; and the fluorine-containing diamine is octafluorodiamine.

[0015] Preferably, the preparation method of starch composite carbon nanotubes is as follows: 300 parts of starch and 90-120 parts of γ-chloropropyltrimethoxysilane are added to an ethanol aqueous solution, and the mixture is rapidly frozen after the reaction, and dried for 24 hours to obtain chloropropylated starch; chloropropylated starch and 80-130 parts of polyepichlorohydrin-dimethylamine are added to an aqueous sodium hydroxide solution, and stirred for reaction at 50°C for 8 hours; the mixture is dried after suction filtration, and washed with deionized water, and then 105-160 parts of carboxyl carbon nanotubes, deionized water and concentrated sulfuric acid are added, and the mixture is stirred for reaction at 50°C for 10 hours, and finally dried after suction filtration to obtain starch composite carbon nanotubes.

[0016] Preferably, the diisocyanate solution is obtained by mixing hexamethylene diisocyanate and 4,4'-dicyclohexylmethane diisocyanate at a mass ratio of 1-3:1-3 at 45°C.

[0017] Preferably, the processing method of the KPU treating agent for scratch-resistant and anti-collision gloves on the gloves is: after the gloves are cleaned, polished and dried, the KPU treating agent precursor is evenly brushed on the surface of the gloves, and finally cured at 70-80°C for 48h to obtain a cured KPU treating agent and a KPU treating agent-treated glove; the brushing thickness of the palm of the glove is 0.8-1.2mm, the fingertip part is 0.6-0.8mm, the finger joint bend is 0.4-0.6mm, the other parts of the finger are 0.6-0.8mm, the back of the hand is 0.4-0.6mm, and the wrist is 0.4-0.6mm; the overall brushing treatment time is 15min.

[0018] The present invention also provides a KPU treating agent for processing scratch-resistant and anti-collision gloves. The preparation raw materials include: 48-55 parts of terminal hydroxyl polyurethane prepolymer, 8.0-12.0 parts of surface-treated ceramic particles, 8.5-14 parts of starch composite carbon nanotubes, 4-8 parts of amino silicone oil, 55-62 parts of terminal amino polyurea prepolymer, 17.8-21.1 parts of diisocyanate solution, and 0.3-0.6 parts of catalyst; the viscosity of the KPU treating agent for processing scratch-resistant and anti-collision gloves is 1500-2500mPa·s; the KPU treating agent for processing scratch-resistant and anti-collision gloves is prepared by any one of the above preparation methods.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. By surface treating the ceramic particles, hydroxyl functional groups are introduced on their surfaces under the action of an initiator, so that during the cross-linking process of component A and component B, the hydroxyl groups can react with isocyanate groups and carboxyl groups in the system, thereby improving the compatibility of the ceramic particles with the system; by combining ceramic particles of different particle sizes and adjusting the amount of surface treated ceramic particles, the gloves treated with the KPU treatment agent have good scratch resistance.

[0021] 2. Starch composite carbon nanotubes were prepared by compounding starch and carbon nanotubes. The starch surface was first grafted with γ-chloropropyltrimethoxysilane, and then reacted with polyepichlorohydrin-dimethylamine to make the starch surface rich in hydroxyl and amino groups. The treated starch was then reacted with carboxylated carbon nanotubes to organically compound the starch and carbon nanotubes. The starch and carbon nanotubes were then added to component A and cross-linked with component B. The addition of starch composite carbon nanotubes improved the scratch resistance of the gloves and the bonding strength between the KPU treatment agent and the gloves. The starch composite carbon nanotubes and the surface-treated ceramic particles synergistically improved the scratch resistance of the gloves.

[0022] 3. By adjusting the molar ratio of raw materials for the preparation of terminal hydroxyl polyurethane prepolymers and optimizing the preparation method of terminal amino polyurea prepolymers, the amount of raw materials used is adjusted, and fluorine-containing raw materials are introduced during the preparation process; the ratio of the two prepolymers obtained in component A is adjusted to improve the anti-collision performance of gloves treated with KPU treatment agent; and the synergistic effect with the added surface-treated ceramic particles and starch-composite carbon nanotubes improves the anti-collision and scratch resistance of the gloves.

[0023] 4. By optimizing the amount of diisocyanate and catalyst in component B, after mixing component B and component A, controlling the mixing speed, and controlling the viscosity of the final KPU treatment agent within a reasonable range, optimizing the coating thickness of the KPU treatment agent on different parts of the gloves, and adjusting the curing temperature, component A and component B can be well cured with the gloves, thereby improving the scratch resistance and anti-collision performance of the gloves. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a graph showing the anti-collision performance test results of Examples 10, 12-14 and Comparative Examples 24-30 of the present invention. DETAILED DESCRIPTION

[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] See also Figure 1 The present invention provides a KPU treating agent for processing scratch-resistant and anti-collision gloves and a preparation method thereof, and the technical scheme is as follows:

[0027] The substance information used in the present invention is as follows: hexamethylene diisocyanate CAS: 822-06-0; 4,4'-dicyclohexylmethane diisocyanate CAS: 5124-30-1; dibutyltin dilaurate CAS: 77-58-7; N,N-dimethylcyclohexylamine CAS: 98-94-2; dimethyl carbonate CAS: 616-38-6; hydrofluoric acid CAS: 7664-39-3; hydroxyethyl acrylate CAS: 818-61-1; itaconic anhydride CAS: 2170-03-8; 1H,1H,8H,8H-octafluoro-3,6-dioxane-1,8-octanediol CAS: 129301-42-4; aminosulfonic acid CAS: 5329-14-6; octafluorodiamine CAS: 355-73-7; benzoyl peroxide (BPO) CAS: 94-36-0;

[0028] The starch used was corn starch; the gloves were purchased from Shandong Xingyu Gloves Co., Ltd.; the amino silicone oil was purchased from Dow Chemical Co., Ltd., model OFX-8040A Dow Corning; and the carboxyl carbon nanotubes were purchased from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd., product model 101369.

[0029] Example 1

[0030] 50 parts of terminal hydroxyl polyurethane prepolymer were added to a reaction kettle, and then 300 parts of dimethyl carbonate were added, the temperature was raised to 50°C, and the stirring device was turned on at the same time, and the mixture was stirred at a speed of 200 rpm for 40 minutes to completely dissolve the terminal amino polyurea prepolymer to obtain a terminal hydroxyl polyurethane prepolymer solution; 9.5 parts of surface-treated ceramic particles were added to the terminal hydroxyl polyurethane prepolymer solution, the rotation speed was increased to 400 rpm, and the mixture was stirred at 60°C for 80 minutes, the temperature was lowered to 50°C, 10 parts of starch composite carbon nanotubes were added, the rotation speed was maintained at 330 rpm, and the stirring was continued for 60 minutes, 5 parts of amino silicone oil were added, and the mixture was stirred at 50°C and 250 rpm for 30 minutes, and finally 60 parts of terminal amino polyurea prepolymer were added, and the mixture was stirred at 45°C for 40 minutes to obtain component A;

[0031] Hexamethylene diisocyanate and 4,4'-dicyclohexylmethane diisocyanate are mixed at a mass ratio of 1:1 at 45°C to obtain a diisocyanate solution, and 19.5 parts of the diisocyanate solution are mixed with 0.25 parts of dibutyltin dilaurate and 0.25 parts of N,N-dimethylcyclohexylamine to obtain component B; dibutyltin dilaurate and, N-dimethylcyclohexylamine are used as catalysts, the mixing mass ratio is 1:1, and the amount is 0.5 parts; component A and component B are mixed, and the KPU treatment agent precursor is obtained by mixing at a speed of 350rpm, and the KPU treatment agent precursor is obtained by diluting with a dimethyl carbonate aqueous solution with a mass concentration of 98% to obtain a KPU treatment agent with a viscosity of 2000mPa·s; after the gloves are cleaned, polished and dried, the KPU treatment agent precursor is evenly applied on the surface thereof, and finally cured at 75°C for 48h to obtain a cured KPU treatment agent and gloves treated with the KPU treatment agent. The thickness of the coating is 1.0mm on the palm, 0.7mm on the fingertips, 0.5mm on the bend of the finger joints, 0.6mm on the rest of the fingers, 0.6mm on the back of the hand, and 0.5mm on the wrist. The total coating time is 15 minutes.

[0032] The preparation method of surface-treated ceramic particles is as follows: Ceramic particles with average particle sizes of 10μm, 50μm and 100μm are mixed in a mass ratio of 13:6:1 to obtain mixed ceramic particles; 40 parts of the weighed mixed ceramic particles are slowly added to a plastic container containing 400 parts of a 5% hydrofluoric acid aqueous solution, stirring with a stirring rod while adding, stirring and reacting for 15 minutes at about 25°C, filtering and washing with deionized water until the pH of the washing liquid is 7, and finally drying to obtain acid-etched ceramic particles. 30 parts of acid-etched ceramic particles are added to 60 parts of hydroxyethyl acrylate, and 0.5 parts of BPO are added. After mixing evenly, react at 60°C for 4 hours until the content of hydroxyethyl acrylate in the solution no longer changes; after cooling to room temperature, wash with deionized water and dry to obtain surface-treated ceramic particles. α-Al in ceramic particles 2 O3 The crystalline phase accounts for 71.2%, TiO 2 The rutile phase accounts for 26.8%, and the rest is SiO 2 Crystal phase, Fe 2 O 3 Crystalline phase and Y 2 O 3 Crystalline substances.

[0033] Embodiment 2-4

[0034] Different from Example 1, the preparation method of the surface-treated ceramic particles and the amount of the surface-treated ceramic particles in component A are changed, as shown in Table 1.

[0035] Table 1 Preparation method and dosage of surface treated ceramic particles

[0036]

[0037] Comparative Example 1

[0038] Different from Example 1, no surface treated ceramic particles were added.

[0039] Comparative Example 2

[0040] Different from Example 1, the ceramic particles are not surface treated.

[0041] Comparative Example 3

[0042] Different from Example 1, only ceramic particles with an average particle size of 10 μm were used.

[0043] Comparative Example 4

[0044] Different from Example 1, only ceramic particles with an average particle size of 50 μm were used.

[0045] Comparative Example 5

[0046] Different from Example 1, only ceramic particles with an average particle size of 100 μm were used.

[0047] Comparative Example 6

[0048] Different from Example 1, the mass ratio of ceramic particles with average particle sizes of 10 μm, 50 μm and 100 μm is 3:4:3.

[0049] Comparative Example 7

[0050] The difference from Example 1 is that the γ-Al 2 O 3 The crystal phase accounts for 54.5%, α-Al 2 O 3 The crystal phase accounts for 17.5%, TiO2 The crystalline phase accounts for 10.5%.

[0051] Comparative Example 8

[0052] Different from Example 1, the acid etching time is 1.5 h.

[0053] Comparative Example 9

[0054] The difference from Example 1 is that surface treated ceramic particles are added and the rotation speed is still maintained at 200 rpm.

[0055] Experimental Example 1

[0056] The gloves treated with KPU treatment agent obtained in the above examples and comparative examples were tested for scratch resistance and flexibility. The scratch resistance was mainly tested with reference to GB / T23766-2009 "Color fastness of leather - reciprocating friction color fastness", using a friction cloth for 2000 times of scratching; the flexibility was tested with reference to the method of GB / T2411-2008 "Determination of indentation hardness Shore hardness of plastics and hard rubber using a hardness tester", and the final test results are shown in Table 2. The scratch level increases from 1 to 4, with 1: indicating the greatest degree of color change; 1-2: the degree of color change is slightly less than that of 1; 2: the color change is more significant; 2-3: the degree of color change is between 2 and 3; 3: there is a visible color change, but the degree of change is relatively small; 3-4: the color change is relatively slight; 4: the color change is very slight.

[0057] Table 2 Performance test results of Examples 1-4 and Comparative Examples 1-9

[0058] Example Scratch resistance level (grade) Shore Hardness Example 1 3 62.5 Example 2 3 61.8 Example 3 3-4 63.4 Example 4 3 63.0 Comparative Example 1 1-2 52.9 Comparative Example 2 2 57.6 Comparative Example 3 1-2 53.3 Comparative Example 4 2 54.0 Comparative Example 5 3-4 68.1 Comparative Example 6 2-3 63.2 Comparative Example 7 2 58.4 Comparative Example 8 2 58.0 Comparative Example 9 2-3 60.1

[0059] The gloves treated with KPU treatment agent of the present invention have scratch resistance levels of 3 and 3-4 and Shore hardness of 61.8-63.4 under the conditions of Examples 1-4. The ceramic particles are surface treated and acid-etched with hydrofluoric acid aqueous solution, and the etching time is controlled within a reasonable range, so as to effectively increase the active sites on the surface of the ceramic particles, improve the roughness of the ceramic particles, and promote the combination of the ceramic particles with the system; the added BPO decomposes to produce free radicals, and the free radicals induce the polymerization reaction of hydroxyethyl acrylate monomer to form a long-chain polymer, and at the same time, the free radicals at one end of the polymer chain react with the active sites on the surface of the ceramic particles to form a carbon-carbon covalent bond, and hydroxyethyl acrylate is grafted on the surface of the ceramic particles. The introduced hydroxyethyl acrylate improves the compatibility of the inorganic particles of the ceramic particles with the components (by reacting with the isocyanate group and carboxyl group in the system after mixing with component B), and on the other hand, makes the gloves both rigid and flexible. Ceramic particles with small particle size have a larger specific surface area and can better combine with the matrix material to make the material structure denser; ceramic particles with medium particle size have a better balance in providing wear resistance and flexibility; ceramic particles with large particle size can provide stronger impact resistance, but reduce the flexibility of the application material; by combining ceramic particles of different particle sizes, optimizing the acid etching time, optimizing the conditions for introducing hydroxyethyl acrylate, and adjusting the amount of surface-treated ceramic particles in component A, the gloves treated with KPU treatment agent have good scratch resistance. In Comparative Example 1, no surface-treated ceramic particles were added, and the scratch resistance was greatly reduced; in Comparative Example 2, the ceramic particles were not surface-treated, the bonding force between the ceramic particles and the organic components decreased, and the scratch resistance decreased, but it was better than the group in Comparative Example 1 in which no surface-treated ceramic particles were added; in Comparative Examples 3-5, only small, medium and large particle size surface-treated ceramic particles were used, respectively. The scratch resistance of Comparative Examples 3 and 4 was worse than that of Example 1, and the scratch resistance of Comparative Example 5 was improved, but the hardness also increased, and protruding particles appeared on the surface of the gloves, and the flexibility of the gloves decreased, which was not conducive to the work use of the gloves; and under the same etching conditions, the surface structure of the small-sized ceramic particles in Comparative Example 3 was destroyed, and the surface etching effect of the large-sized ceramic particles in Comparative Example 5 was worse, which was not conducive to improving the scratch resistance of the final gloves; in Comparative Example 6, the surface-treated ceramic particles of the three particle sizes were not properly matched, which also made the scratch resistance level lower than that of Example 1; in Comparative Example 7, the γ-Al 2 O 3 The proportion of crystalline phase increases, TiO 2 The proportion of crystalline phase decreases, γ-Al 2 O 3 It belongs to the cubic crystal system and has a defective spinel structure. There are many vacancies in its lattice and the atomic arrangement is relatively loose, which reduces the stability of the ceramic particles. 2The proportion of the crystalline phase is reduced, the density of the system is reduced, and the rutile phase itself can provide a higher hardness, which improves the scratch resistance of the material. The reduced content also reduces the scratch resistance of the gloves. The acid etching time of Comparative Example 7 is too long, which is not conducive to the improvement of the performance of the gloves after KPU treatment. The rotation speed of Comparative Example 9 is too low, which is not conducive to the stable dispersion of the surface-treated ceramic particles in the system, and the cross-linking is uneven during the subsequent curing process, and the scratch resistance of the final material is reduced.

[0060] Embodiment 5-8

[0061] The preparation method of starch composite carbon nanotubes is as follows: 300 parts of starch and 90-120 parts of γ-chloropropyltrimethoxysilane are added to 240 parts of ethanol aqueous solution with a mass concentration of 20%, mixed evenly at a speed of 500rpm, and stirred at 50°C for reaction for 4h; filtered after the reaction, quickly frozen, and dried for 24h to obtain chloropropylated starch; chloropropylated starch and 80-130 parts of polyepichlorohydrin-dimethylamine with a molecular weight of 150,000 are added to 1000 parts of sodium hydroxide aqueous solution with a mass concentration of 10%, and stirred at 50°C for reaction for 8h; dried after suction filtration, and washed with deionized water, and then 105-160 parts of carboxyl carbon nanotubes, 1000 parts of deionized water and 1 part of concentrated sulfuric acid are added, stirred at 50°C for reaction for 10h, and finally dried after suction filtration to obtain starch composite carbon nanotubes.

[0062] Different from Example 3, the preparation method of starch composite carbon nanotubes, the amount of component A and the temperature change of adding starch composite carbon nanotubes are specifically shown in Table 3. The temperature in Table 3 is the temperature of the system before adding starch composite carbon nanotubes; the speed is the speed after adding starch composite carbon nanotubes.

[0063] Table 3 Preparation method and dosage of starch composite carbon nanotubes

[0064]

[0065] Comparative Example 10

[0066] Different from Example 3, γ-chloropropyltrimethoxysilane was not added.

[0067] Comparative Example 11

[0068] Different from Example 3, polyepichlorohydrin-dimethylamine was not added.

[0069] Comparative Example 12

[0070] Different from Example 3, no carboxyl carbon nanotubes were added.

[0071] Comparative Example 13

[0072] The difference from Example 3 is that the temperature is 65°C.

[0073] Comparative Example 14

[0074] Different from Example 3, no starch composite carbon nanotubes were added.

[0075] Comparative Example 15

[0076] The difference from Example 3 is that neither starch-composite carbon nanotubes nor surface-treated ceramic particles are added.

[0077] Comparative Example 16

[0078] The difference from Example 3 is that the rotation speed is 400 rpm.

[0079] Experimental Example 2

[0080] The gloves treated with KPU treatment agent in the above embodiment and comparative example were subjected to scratch resistance test, and the test method was carried out with reference to Experimental Example 1; the bonding strength test was carried out with reference to GB / T5210-2006 "Pull-off Adhesion Test for Paints and Varnishes", and samples were taken from the palm, fingertips, bends of finger joints, back of hand, wrist and other parts of the gloves to test the bonding strength, and the bonding strength was taken as the average value of the above six parts. The test results are shown in Table 4.

[0081] Table 4 Test results of bonding strength and scratch resistance

[0082] Scratch resistance level (grade) Bond strength (MPa) Example 3 3-4 2.5 Example 5 4 3.2 Example 6 3-4 3.0 Example 7 4 2.3 Example 8 3-4 2.5 Comparative Example 10 2-3 2.3 Comparative Example 11 2-3 2.5 Comparative Example 12 1-2 2.5 Comparative Example 13 1-2 2.0 Comparative Example 14 2-3 1.4 Comparative Example 15 1 1.2 Comparative Example 16 3-4 2.1

[0083] The gloves treated with the KPU treating agent obtained in the present invention have scratch resistance levels of 3-4 and 4 under the conditions of Examples 3 and 5-8, and a bonding strength of 2.3-3.0 MPa. First, chloropropylated starch is prepared. The starch molecule contains a large number of hydroxyl groups. After adding γ-chloropropyltrimethoxysilane, the methoxy groups therein undergo a hydrolysis reaction in an ethanol aqueous solution to generate silanol groups. The silanol groups undergo a condensation reaction with the hydroxyl groups on the starch molecules to form silicon-oxygen bonds, thereby introducing chloropropyl groups into the starch molecules. Then, in an alkaline environment, the activity of the chlorine atom of the chloropropyl group is increased, and a nucleophilic substitution reaction occurs with the amine group of epichlorohydrin-dimethylamine. The lone pair of electrons contained in the nitrogen atom of the amine group attacks the chlorine atom on the chloropropyl group, causing the chlorine atom to leave in the form of chloride ions, thereby forming a composite structure of starch-chloropropyl-epichlorohydrin-dimethylamine. The chloropropyl-epichlorohydrin-dimethylamine contains abundant hydroxyl groups and amino groups, and the starch molecules themselves contain a large number of hydroxyl groups, which then undergo a polar esterification reaction and a condensation reaction with the carboxyl group of the carboxylated carbon nanotubes to obtain starch composite carbon nanotubes. The starch composite carbon nanotubes then react with the isocyanate groups in the system to achieve the effect of cross-linking. The hydroxyl groups of starch have strong polarity. In the system of KPU-treated gloves, the hydroxyl groups of starch can form hydrogen bonds with the polar groups in the KPU treatment agent and the polar groups on the surface of the glove matrix material, and some oxygen-containing groups in the rubber, thereby enhancing the interaction between the starch and the KPU treatment agent and the glove matrix, and improving the bonding force; the subsequent starch gelatinization forms a film to form a continuous film on the surface of the glove, further improving the bonding effect between the KPU treatment agent and the glove; when subjected to scratching force, the carbon nanotubes can withstand most of the stress, disperse and transmit the energy generated during the scratching process, avoid stress concentration in local areas to cause coating damage, and can effectively improve the deformation resistance of the glove surface coating and reduce the occurrence of scratch damage. In the scratching process, the carbon nanotubes can play a role similar to a lubricant, reducing the friction between the coating and the scratching object, thereby reducing the heat and wear generated during the scratching process, thereby reducing the degree of damage to the coating. The above preparation method is optimized so that the gloves treated with the KPU treating agent have good scratch resistance and high bonding strength between the KPU treating agent and the gloves.Comparative Examples 10 and 11 did not add γ-chloropropyltrimethoxysilane and polyepichlorohydrin-dimethylamine, respectively, and could not provide more hydroxyl and amino groups for the system, so the subsequent cross-linking degree was reduced, which in turn had a poor effect on the scratch performance; Comparative Example 12 did not add carboxyl carbon nanotubes, and the bonding strength did not change significantly, but the scratch resistance level decreased; Comparative Example 13 had a temperature of 65°C, the starch gelatinized in advance, the dispersibility in component A was greatly reduced, and the cross-linking performance decreased after adding component B, so the bonding strength decreased, and the distribution in the system was uneven after curing, and the scratch resistance was also reduced; Comparative Example 14 did not add starch composite carbon nanotubes, and both the bonding strength and the scratch resistance level were reduced; The results of Comparative Example 15 show the beneficial effect of the co-treatment of starch composite carbon nanotubes and surface-treated ceramic particles on the scratch resistance; Comparative Example 16 had a rotation speed that was too high, the starch was easy to agglomerate, which was not conducive to the subsequent reaction, and the bonding strength was reduced.

[0084] Examples 9-11

[0085] The preparation method of the hydroxyl-terminated polyurethane prepolymer is as follows: polypropylene glycol with a degree of polymerization of 20 and 1,4-cyclohexanediol with a degree of polymerization of 5 are vacuum dehydrated at 100°C for 3 hours to remove the moisture therein; the dehydrated polypropylene glycol and 1,4-cyclohexanediol are mixed with hexamethylene diisocyanate, dibutyltin dilaurate is added, and then acetone (20 times the total volume of polypropylene glycol, 1,4-cyclohexanediol and hexamethylene diisocyanate) is added, nitrogen is introduced after mixing, air is excluded, and the stirrer is turned on, and the stirring speed is controlled to The mixture is controlled at 300 rpm to fully mix the materials to obtain a polymer to be polymerized; the temperature is slowly raised to 80° C. to start the reaction. After the reaction for 4 hours, the content of isocyanate groups in the system no longer changes. Then, polyethylene glycol with a degree of polymerization of 10 is added. After the reaction is continued for 3 hours, the organic solvent is removed by reduced pressure distillation to obtain a hydroxyl-terminated polyurethane prepolymer; the mixing molar ratio of polypropylene glycol, cyclohexanediol, hexamethylene diisocyanate, polyethylene glycol and dibutyltin dilaurate is 5-7:3-5:11-12:1-3:0.005;

[0086] The preparation method of the amino-terminated polyurea prepolymer is as follows: itaconic anhydride and 1H,1H,8H,8H-octafluoro-3,6-dioxane-1,8-octanediol are added to a three-necked flask at a molar ratio of 1:2-2.3, and after being stirred evenly, a catalyst aminosulfonic acid (0.5%-5% of the total volume of maleic anhydride and fluorinated alcohol) and a water-carrying agent toluene (40% of the total volume of the reactants) are added. Water is produced during the reaction and is removed through a water separator. After the reaction is completed for 6 hours, no water droplets are produced. After the reaction is completed, toluene is removed to obtain fluorinated itaconate; fluorinated diamine-octafluorodiamine is added to a four-necked flask, stirred at a speed of 500 rpm, and the temperature is maintained at 45°C. After the fluorinated diamine is melted, the fluorinated itaconate is added dropwise, and the molar ratio of the fluorinated diamine to the fluorinated itaconate is 1:2-2.2. The temperature is raised to 60°C and the reaction is performed for 5 hours to obtain the amino-terminated polyurea prepolymer;

[0087] Different from Example 5, the preparation method of the hydroxyl-terminated polyurethane prepolymer and the amino-terminated polyurea prepolymer and the amount used in the system are changed, as shown in Table 5. The four substances in Table 5 are polypropylene glycol, cyclohexanediol, hexamethylene diisocyanate and polyethylene glycol.

[0088] Comparative Example 17

[0089] Different from Example 5, polyethylene glycol is not added last, but is added together with polypropylene glycol and cyclohexanediol.

[0090] Comparative Example 18

[0091] The difference from Example 5 is that the fluorine-containing alcohol is replaced by octanediol.

[0092] Comparative Example 19

[0093] The difference from Example 5 is that the fluorine-containing diamine is replaced by hexamethylenediamine.

[0094] Comparative Example 20

[0095] The difference from Example 5 is that the amount of the hydroxyl-terminated polyurethane prepolymer added is 110 parts, and the amino-terminated polyurea prepolymer is not added.

[0096] Comparative Example 21

[0097] The difference from Example 5 is that the amount of amino-terminated polyurea prepolymer added is 110 parts, and no hydroxyl-terminated polyurethane prepolymer is added.

[0098] Comparative Example 22

[0099] Different from Example 5, no amino silicone oil was added.

[0100] Comparative Example 23

[0101] The difference from Example 5 is that the amino-terminated polyurea prepolymer is replaced by hexamethylenediamine.

[0102] Table 5 Preparation method and dosage of hydroxyl-terminated polyurethane prepolymer and amino-terminated polyurea prepolymer

[0103]

[0104] Experimental Example 3

[0105] The gloves treated with KPU treatment agent obtained in the above examples and comparative examples were tested for anti-collision performance and scratch resistance. The scratch resistance was tested according to the method of Experimental Example 1; the anti-collision performance test method is as follows: at 23°C and a relative humidity of 52%, the gloves were placed vertically above a metal cylinder with a mass of 1kg at a height of 5m, and recorded using a high-speed camera and a pressure sensor, and the energy of the gloves before and after the impact was calculated. Where η is the energy absorption rate, E0 is the energy before impact, and E1 is the remaining energy after impact. The final results are shown in Table 6.

[0106] Table 6 Impact performance and scratch performance test results

[0107] η(%) Scratch resistance level (grade) Example 5 45.4 4 Example 9 45.0 4 Example 10 46.5 4 Embodiment 11 46.1 4 Comparative Example 1 22.1 1-2 Comparative Example 14 25.6 2-3 Comparative Example 15 16.3 1 Comparative Example 17 40.9 3 Comparative Example 18 41.7 2-3 Comparative Example 19 41.9 2-3 Comparative Example 20 37.9 2-3 Comparative Example 21 39.5 3 Comparative Example 22 45.2 3-4 Comparative Example 23 42.3 1-2

[0108] The gloves treated with the KPU treating agent prepared by the present invention have η of 45.0%-46.5% under the conditions of Example 5 and Examples 9-11, and the scratch resistance grade is Level 4. During the preparation of the hydroxyl-terminated polyurethane prepolymer, the isocyanate group of hexamethylene diisocyanate reacts with the hydroxyl groups of polypropylene glycol and 1,4-cyclohexanediol to form a carbamate bond (-NH-COO-), thereby connecting the polyol and the diisocyanate to form a prepolymer containing an isocyanate end group. The molar ratio of polypropylene glycol, cyclohexanediol, hexamethylene diisocyanate and polyethylene glycol is adjusted. First, the amount of alkyl group and cyclohexane group in the diol is moderate, thereby improving the hardness and toughness of the material treated with the KPU treatment agent. Finally, polyethylene glycol is added to continue the reaction. The hydroxyl group of polyethylene glycol continues to undergo amination reaction with the isocyanate group in the prepolymer containing an isocyanate end group formed previously, thereby further increasing the molecular chain, and finally obtaining a hydroxyl-terminated polyurethane prepolymer. Since the amount of isocyanate group is relatively less than that of the polyol, polyethylene glycol is added in the later stage of the reaction, so that both ends of the final product molecule are hydroxyl groups, thereby making it cross-linked with the isocyanate group in component B, thereby improving the toughness of the material and thus improving the impact resistance of the material. Itaconic anhydride and 1H,1H,8H,8H-octafluoro-3,6-dioxane-1,8-octanediol react in the presence of aminosulfonic acid as a catalyst and toluene as a water-carrying agent, wherein the anhydride undergoes a ring-opening esterification reaction with the alcohol to obtain a fluorinated itaconate, a fluorinated diamine is added into a four-necked flask and stirred to melt, and then the fluorinated itaconate is added dropwise, the amino group of the fluorinated diamine undergoes a nucleophilic addition-elimination reaction with the carbonyl group in the fluorinated itaconate to form a urea bond, and then a gel is formed in the cross-linking process, and finally completely solidified, and at the same time, the group contained in the formed amino-terminated polyurea prepolymer is -NH- instead of -NH 2, the curing reaction speed is greatly reduced during the curing process with component B, so that the use of KPU treatment agent to brush the gloves is less time-restricted. In comparative example 23, the amino-terminated polyurea prepolymer is replaced with hexamethylenediamine, and the impact resistance of the material is lower than that of Example 9. Due to the fast curing reaction process, the KPU treatment agent has already cured during the 15-minute coating process, and the subsequent curing is uneven, resulting in a significant decrease in scratch resistance. In comparative example 1, no surface-treated ceramic particles are added, and in comparative example 14, no starch-composite carbon nanotubes are added, and the energy absorption rate is reduced; the addition of the above components not only improves the scratch resistance of the gloves, but also improves the density and toughness of the system. The addition of surface-treated ceramic particles, starch-composite carbon nanotubes, hydroxyl-terminated polyurethane prepolymers and amino-terminated polyurea prepolymers synergistically improves the impact resistance and scratch resistance of the gloves. In comparative example 15, neither starch-composite carbon nanotubes nor surface-treated ceramic particles are added, and the performance of the gloves is further reduced. In Comparative Example 17, polyethylene glycol is not added last, which reduces the content of hydroxyl groups at the molecular endpoints of the terminal hydroxyl polyurethane prepolymer. In the subsequent curing process, there are fewer curing active sites and the performance is reduced. In Comparative Examples 18 and 19, fluorine-containing alcohols and fluorine-containing diamines are not used, and fluorine atoms are not introduced into the system. When fluorine atoms are introduced into the material, the fluorine atoms on the surface of the material are arranged outward to form a surface with low surface energy, so that the surface of the material is not easy to be attached by other substances. When scratched, the friction between foreign objects and the surface of the material is reduced; at the same time, the tight structure formed can better resist the damage of external forces and reduce the generation of scratches; the presence of fluorine atoms will affect the conformation and mobility of the molecular chain, making the molecular chain have a certain flexibility. When the material is impacted, this flexibility can make the material better absorb and disperse the impact energy, thereby reducing the damage to the material; therefore, the scratch resistance and impact resistance of the gloves in Comparative Examples 18 and 19 are reduced. In Comparative Examples 20 and 21, only hydroxyl-terminated polyurethane prepolymers and amino-terminated polyurea prepolymers are used, respectively, and the performance of the gloves is reduced. In Comparative Example 22, amino silicone oil was not added, the content of substances reacting with isocyanate was reduced, and the lubricating performance of the KPU treatment agent was reduced, so the scratch resistance was reduced.

[0109] Examples 12-14

[0110] Different from Example 10, the following parameters are changed, as shown in Table 7. The two diisocyanates in Table 7 are hexamethylene diisocyanate and 4,4'-dicyclohexylmethane diisocyanate; the six parts in Table 7 are the palm, the fingertips, the bend of the finger joints, other parts of the fingers, the back of the hand and the wrist.

[0111] Comparative Example 24

[0112] In contrast to Example 10, only hexamethylene diisocyanate was used.

[0113] Comparative Example 25

[0114] Unlike Example 10, only 4,4'-dicyclohexylmethane diisocyanate was used.

[0115] Comparative Example 26

[0116] The difference from Example 10 is that the viscosity of the KPU treatment agent is 800 mPa·s.

[0117] Comparative Example 27

[0118] The difference from Example 10 is that the viscosity of the KPU treatment agent is 4000 mPa·s.

[0119] Comparative Example 28

[0120] The difference from Example 10 is that the curing temperature is 120°C.

[0121] Comparative Example 29

[0122] Different from Example 10, the KPU coating thickness of the six parts is 1.2 mm.

[0123] Comparative Example 30

[0124] Different from Example 10, the KPU coating thickness of the six parts is 0.4 mm.

[0125] Table 7 Mixing conditions and coating conditions of component A and component B

[0126]

[0127] Experimental Example 4

[0128] The gloves treated with KPU treatment agent obtained in the above examples and comparative examples were tested for scratch resistance and collision resistance. The final test results are shown in Table 8 and Figure 1 shown.

[0129] Table 8 Scratch resistance and anti-collision performance test results of Example 10, Examples 12-14 and Comparative Examples 24-30

[0130]

[0131]

[0132] As shown in Table 8 and Figure 1As shown, the KPU treatment agent prepared by the present invention is used to treat gloves. Under the conditions of Example 10 and Examples 12-14, η is 46.5%-47.5%, and the scratch resistance level is level 4. By optimizing the mixing mass ratio of hexamethylene diisocyanate and 4,4'-dicyclohexylmethane diisocyanate in component B, the alkyl flexible segment and the cyclohexane rigid segment are reasonably introduced after the hydroxyl and amino groups contained in component A react with the isocyanate group, thereby improving the toughness and anti-collision performance of the material; by optimizing the mixing speed and the viscosity of the KPU treatment agent, and optimizing the thickness of the KPU treatment agent applied to different glove regions according to the different contact areas between different parts of the gloves and the material during actual use, the gloves are ensured to have good scratch resistance and anti-collision effects while ensuring the convenience of the gloves in actual use and reducing the amount of raw materials. Comparative Examples 24 and 25 use one type of diisocyanate respectively, and the scratch resistance level and energy absorption rate are reduced; Comparative Example 26 KPU treatment agent has low viscosity and low effective component content, which is not conducive to improving the performance of gloves; Comparative Example 27 KPU treatment agent has high viscosity and the effective component content is increased compared with the embodiment, but it is not conducive to brushing, the curing is not complete, and the scratch resistance and anti-collision performance of the gloves are reduced. Comparative Example 28 The curing temperature is too high, dimethyl carbonate evaporates quickly, the curing is incomplete, and the gloves are slightly deformed, and the glove performance is reduced. Comparative Example 29 The coating thickness is increased. Although the energy absorption rate is increased, the coating thickness is high, which is not conducive to saving raw materials. In addition, the sensitivity and convenience of the gloves are reduced. Comparative Example 30 The KPU coating thickness is too low, and the scratch resistance and anti-collision performance of the gloves are deteriorated.

[0133] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a KPU treating agent for processing scratch-resistant and collision-resistant gloves, characterized in that: The preparation method is as follows: Add 8.0-12.0 parts of surface-treated ceramic particles to 48-55 parts of hydroxyl-terminated polyurethane prepolymer and dimethyl carbonate, increase the rotation speed to 400 rpm, lower the temperature to 40-50° C. after stirring, add 8.5-14 parts of starch composite carbon nanotubes, keep the rotation speed at 250-330 rpm, continue stirring, add 4-8 parts of amino silicone oil, stir at 50° C. and 250 rpm for 30 minutes, finally add 55-62 parts of amino-terminated polyurea prepolymer, stir and mix to obtain component A; 17.8-21.1 parts of diisocyanate solution and 0.3-0.6 parts of catalyst are mixed to obtain component B; the component A and the component B are mixed evenly at a speed of 350-450 rpm to obtain a KPU treatment agent precursor; the KPU treatment agent precursor is diluted to a viscosity of 1500-2500 mPa·s to obtain the KPU treatment agent for processing scratch-resistant and anti-collision gloves; The amino-terminated polyurea prepolymer is obtained by reacting itaconic anhydride, fluorine-containing alcohol and fluorine-containing diamine; the hydroxyl-terminated polyurethane prepolymer is obtained by reacting polypropylene glycol, 1,4-cyclohexanediol, hexamethylene diisocyanate and polyethylene glycol; and the starch composite carbon nanotube is obtained by reacting starch, γ-chloropropyltrimethoxysilane, polyepichlorohydrin-dimethylamine and carboxyl carbon nanotube.

2. The method for preparing a KPU treating agent for processing scratch-resistant and anti-collision gloves according to claim 1, characterized in that: The preparation method of the surface-treated ceramic particles is as follows: ceramic particles with average particle sizes of 10 μm, 50 μm and 100 μm are mixed in a mass ratio of 5-14:4-10:1 to obtain mixed ceramic particles; the mixed ceramic particles are acid-etched using a 5% hydrofluoric acid aqueous solution, reacted for 15-25 minutes, filtered, washed with water and dried to obtain acid-etched ceramic particles; 30 parts of the acid-etched ceramic particles are added to 40-60 parts of hydroxyethyl acrylate, and 0.2-0.5 parts of benzoyl peroxide are added, mixed evenly, reacted at 60-80° C. for 2-4 hours; after cooling to room temperature, washed with water and dried to obtain the surface-treated ceramic particles.

3. The method for preparing a KPU treating agent for processing scratch-resistant and collision-resistant gloves according to claim 2, characterized in that: The α-Al2O3 crystal phase accounts for 71.2% of the ceramic particles, and the TiO2 rutile crystal phase accounts for 26.8%.

4. The method for preparing a KPU treating agent for processing scratch-resistant and collision-resistant gloves according to claim 1, characterized in that: The preparation method of the terminal hydroxyl polyurethane prepolymer is as follows: polypropylene glycol and 1,4-cyclohexanediol are mixed with hexamethylene diisocyanate and reacted, polyethylene glycol is added after the reaction is completed, and the reaction is continued for 3 hours to obtain the terminal hydroxyl polyurethane prepolymer; the mixing molar ratio of the polypropylene glycol, the 1,4-cyclohexanediol, the hexamethylene diisocyanate and the polyethylene glycol is 5-7:3-5:11-12:1-3.

5. The method for preparing a KPU treating agent for processing scratch-resistant and collision-resistant gloves according to claim 1, characterized in that: The preparation method of the amino-terminated polyurea prepolymer is as follows: add the itaconic anhydride and the fluorine-containing alcohol in a three-necked flask at a molar ratio of 1:2-2.3, stir evenly, add aminosulfonic acid and toluene, remove the water generated during the reaction through a water separator, remove the toluene after the reaction to obtain the fluorine-containing itaconate; add the fluorine-containing itaconate dropwise to the melted fluorine-containing diamine; the molar ratio of the fluorine-containing diamine to the fluorine-containing itaconate is 1:2-2.2, heat to 60°C, react for 5 hours to obtain the amino-terminated polyurea prepolymer; the fluorine-containing alcohol is 1H,1H,8H,8H-octafluoro-3,6-dioxa-1,8-octanediol; the fluorine-containing diamine is octafluorodiamine.

6. The method for preparing a KPU treating agent for processing scratch-resistant and collision-resistant gloves according to claim 1, characterized in that: The preparation method of the starch composite carbon nanotubes is as follows: 300 parts of the starch and 90-120 parts of the γ-chloropropyltrimethoxysilane are added to an ethanol aqueous solution, and after the reaction, they are quickly frozen and dried for 24 hours to obtain chloropropylated starch; the chloropropylated starch and 80-130 parts of the polyepichlorohydrin-dimethylamine are added to a sodium hydroxide aqueous solution, and stirred for reaction at 50°C for 8 hours; after filtration, they are dried and washed with deionized water, and then 105-160 parts of the carboxyl carbon nanotubes, the deionized water and concentrated sulfuric acid are added, and the reaction is stirred for 10 hours at 50°C, and finally, after filtration, they are dried to obtain the starch composite carbon nanotubes.

7. The method for preparing a KPU treating agent for processing scratch-resistant and collision-resistant gloves according to claim 1, characterized in that: The diisocyanate solution is obtained by mixing hexamethylene diisocyanate and 4,4'-dicyclohexylmethane diisocyanate at a mass ratio of 1-3:1-3 at 45°C.

8. The method for preparing a KPU treating agent for processing scratch-resistant and collision-resistant gloves according to claim 1, characterized in that: The processing method of the KPU treating agent for scratch-resistant and anti-collision gloves is as follows: after the gloves are cleaned, polished and dried, the KPU treating agent precursor is evenly brushed on the surface of the gloves, and finally cured at 70-80°C for 48 hours to obtain the cured KPU treating agent and the gloves treated with the KPU treating agent; the coating thickness of the palm of the gloves is 0.8-1.2mm, the fingertip part is 0.6-0.8mm, the finger joint bend is 0.4-0.6mm, the other parts of the fingers are 0.6-0.8mm, the back of the hand is 0.4-0.6mm, and the wrist part is 0.4-0.6mm; the overall brushing time is 15min.

9. A KPU treating agent for processing scratch-resistant and collision-resistant gloves, characterized in that: The preparation raw materials include: 48-55 parts of terminal hydroxyl polyurethane prepolymer, 8.0-12.0 parts of surface-treated ceramic particles, 8.5-14 parts of starch composite carbon nanotubes, 4-8 parts of amino silicone oil, 55-62 parts of terminal amino polyurea prepolymer, 17.8-21.1 parts of diisocyanate solution, and 0.3-0.6 parts of catalyst; the viscosity of the KPU treatment agent for processing scratch-resistant and anti-collision gloves is 1500-2500mPa·s; the KPU treatment agent for processing scratch-resistant and anti-collision gloves is prepared by the preparation method described in any one of claims 1 to 8.